Rescue endovascular thrombectomy in patients with progressive ischemic stroke within 24–72 h: A retrospective propensity score matched cohort study - Yanchun Wang; Jianzhong Shu; Minghua Tao; Mingshan Tang; Chende Pan; Dinghao Zhen; Jie Wang (Interdisciplinary Neurosurgery, 2023)
Purpose: Currently, the prediction of progressive ischemic stroke (PIS) caused by large proximal artery occlusion (LVO) is not well developed. The main aim of the study is to check the effectiveness of endovascular thrombectomy(EVT) in patients with PIS and LVO in the anterior circulation. Methods: This multicenter retrospective cohort study involved two comprehensive stroke centres having two therapeutic approaches to manage patients with minor, mild, or acute ischemic stroke harbouring LVO. Some patients who experienced early neurologic deterioration (END) were either given the best medical care (BMM) or immediate rescue endovascular thrombectomy (RET) followed by BMM. Clinical outcomes, including good prognosis defined as 90-day modified Ranking Scale (mRS) ≤ 2, mortality, and symptomatic intracerebral hemorrhagic (sICH) rate were compared between two groups. Results: The study included 103 patients, including 48 patients in the RET + BMM group and 55 patients in the BMM group, and each group included 35 patients after propensity score matching. Compared to the BMM group, RET-treated patients had lower 90-day mRS scores at discharge (57.14% vs. 37.14%, p < 0.001). No significant differences in mortality (p = 0.315) and symptomatic intracranial haemorrhage (p = 0.487) were found. Similar results were obtained after propensity score matching. Conclusion: RET appears to be safe and feasible in patients with PIS due to LVO within 24–72 h. Further prospective, clinical, randomized controlled studies are warranted to validate these findings.